Room temperature co-precipitation of nanocrystalline CeO2 and Ce0.8Gd0.2O1.9-delta powder - Godinho, M. J.; Goncalves, R. F.; Santos, L. P. S.; Varela, José Arana [UNESP]; Longo, Elson [UNESP]; Leite, E. R. (Elsevier B.V., 2007)
This paper describes a simple method to co-precipitate CeO2 and Ce0.8Gd0.2O1.9-delta with ammonium hydroxide from solvents such as: water, ethylene glycol, ethyl alcohol and isopropyl alcohol. Characterization by Raman spectroscopy and XRD evidenced the formation of a solid solution of gadolinium-doped ceria at room temperature. Nanometric particles with crystallite size of 3.1 nm were obtained during synthesis using ethyl alcohol as solvent. This is a promising result compared with those mentioned in the literature, in which the smallest crystallite size reported was, 6.5 nm. (c) 2006 Elsevier B.V. All rights reserved.